1997
DOI: 10.1182/blood.v89.4.1224
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Thrombocytopenic Purpura and Sporadic Hemolytic-Uremic Syndrome Plasmas Induce Apoptosis in Restricted Lineages of Human Microvascular Endothelial Cells

Abstract: Thrombotic thrombocytopenic purpura (TTP) and sporadic hemolytic-uremic syndrome (HUS) are thrombotic microangiopathies that occur in the absence of an inflammatory response. Ultrastructural features of tissues involved in TTP/sporadic HUS suggest an apoptotic process. Consistent with these findings, we observed that TTP plasmas induce apoptosis in primary human endothelial cells (EC) of dermal microvascular but not umbilical vein origin (Laurence et al, Blood 87:3245, 1996). We now document the ability of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
87
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 43 publications
8
87
1
Order By: Relevance
“…Although Fas is expressed in EC (6), little is known about the role of the Fas/FasL system on these cells. Previous in vitro reports suggest that Fas ligation does not lead to induction of EC apoptosis (6); however, there is some in vivo evidence suggesting that the Fas/FasL system may be involved in inducing the death of EC in different organs (17,18,32). There are reports that animals receiving anti-Fas mAb, which acts as an agonist of Fas, or soluble FasL die 6 h after injection due to liver necrosis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although Fas is expressed in EC (6), little is known about the role of the Fas/FasL system on these cells. Previous in vitro reports suggest that Fas ligation does not lead to induction of EC apoptosis (6); however, there is some in vivo evidence suggesting that the Fas/FasL system may be involved in inducing the death of EC in different organs (17,18,32). There are reports that animals receiving anti-Fas mAb, which acts as an agonist of Fas, or soluble FasL die 6 h after injection due to liver necrosis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibition of serum antibody binding to microvascular endothelial cells by a blocking CD36 antibody was observed, supporting the idea that, at least in some patients, anti-CD36 antibodies are generated and may contribute to the microvascular lesion observed in TTP. Since Laurence et al (1996) and Mitra et al (1997) have demonstrated that plasmas from TTP patients can induce apoptosis in cultured HMVEC, our analysis focused on non-apoptotic endothelial cells only. We found that some TTP sera also showed strong reactivity to HUVEC, and many of the sera tested exhibited some reactivity to both types of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…TTP and HUS are felt to be different spectra of the same disease process consisting of abnormal formation of platelet and microthrombi in small vessels, coined thrombotic microangiopathy [1]. Typically, these syndromes are reported to spare the lungs [2][3][4][5]. However, as this brief report will show, there are data to the contrary.…”
Section: Introductionmentioning
confidence: 99%